2019
DOI: 10.1063/1.5132698
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition induced spectral tuning of dual luminescent crystalline zinc-phthalocyanine thin films and OLEDs

Abstract: We analyze the impact of the first order structural phase transition between the α- and β-phases in crystalline zinc-phthalocyanine thin films on their luminescent behavior. Upon optical excitation, two intensity maxima governing the dual fluorescence can be attributed to thin film excimer emission of the α-phase at 930 nm and bulk Frenkel exciton emission of the corresponding β-phase at 780 nm. Comprehensive temperature and time dependent studies on the structural phase transition reveal a controllable shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…Our PL data for β-ZnPc and β-CuPc agree well in energy and spectral shape with what has been published previously. , Also, it has been mentioned that for β-NiPc crystals no PL signal could be observed …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our PL data for β-ZnPc and β-CuPc agree well in energy and spectral shape with what has been published previously. , Also, it has been mentioned that for β-NiPc crystals no PL signal could be observed …”
Section: Resultssupporting
confidence: 91%
“…Our PL data for β-ZnPc and β-CuPc agree well in energy and spectral shape with what has been published previously. 35,36 Also, it has been mentioned that for β-NiPc crystals no PL signal could be observed. 35 Thus, while ZnPc, CuPc and NiPc show virtually identical absorption and emission spectra in isolated molecular state, the optical absorption in the β-phase is visibly different, and the PL emission differs tremendously.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Both α-phase and β-phase ZnPc have significant differences in their optical properties. 8,12,14,24–27 For instance, it has been shown that during the α-to-β phase-transition process, the absorbance of the thin film from the ultraviolet to the near-infrared regions can be enlarged by 1.5 to 2 times, which has been attributed to the increment in the angle between the molecular plane and the incident direction of the light. 27 In addition, both phases exhibit two absorption peaks in the Q-band region, but along with the phase transition, it is remarkable that the relative intensities of the two peaks are reversed.…”
Section: Introductionmentioning
confidence: 99%
“…It is nominated as tunable dual luminescent organic light‐emitting diodes. [ 1 ] ZnPc and its derivatives are also used as ambipolar devices. [ 2 ] These devices display a current on/off ratio of 10 5 .…”
Section: Introductionmentioning
confidence: 99%